Pengaruh Ambulasi Dini terhadap Peningkatan ADL pada Pasien Post-Kateterisasi Jantung - Damansyah, Haslinda; Yunus, Pipin; Indrianingsih, Sofiyah Tri; Tui, Lianti (PSIK FKKMK UGM, 2024)
Background: One of the methods to improve activity of daily living (ADL) in post-cardiac catheterization patient is through early ambulation. Usually post-cardiac catheterization patient restricts their activities, which prolongs the recovery process and ADL’s improvement.Objective: To analyze the effect of early ambulation on improving the ADL in post-cardiac catheterization patient.Method: The research design was quantitative pre-experimental study with one-group pre-post experiment design without control group. The sample consisted of 15 respondents selected through accidental sampling method. Respondents were chosen based on the inclusion criteria, i.e.: patient which was treated in the CVCU room and patient of post-cardiac catheterization. Exclusion criteria included patient with decreased consciousness. Data analysis was performed using the non-parametric Wilcoxon statistical test.Results: Before the intervention, most of respondents experienced moderate to severe dependence with a median of 9 (7-11). After the intervention, most of respondents experienced mild to moderate dependence with a median of 12 (11-16). It indicated that there was an improvement in patient independence in ADL with a p-value = 0.000.Conclusion: The early ambulation intervention effectively improves the independency of post-cardiac catheterization surgery patient in performing ADL. Therefore, this intervention should be given to patient with similar condition in order to hasten the recovery process.INTISARILatar belakang: Salah satu cara meningkatkan activity of daily living (ADL) pada pasien post-kateterisasi jantung adalah dengan tindakan ambulasi dini. Umumnya pasien post-operasi kateterisasi jantung masih sering melakukan pembatasan aktivitas, sehingga proses pemulihan dan peningkatan ADL membutuhkan waktu yang semakin lama.Tujuan: Melakukan analisis pengaruh ambulasi dini terhadap peningkatan ADL pada pasien post-kateterisasi jantungMetode: Desain penelitian adalah kuantitatif pra-eksperimen dengan rancangan one grup experiment pre-post tanpa kelompok kontrol. Sampel pada penelitian ini berjumlah 15 responden dengan metode accidental sampling. Responden dipilih berdasarkan kriteria inklusi, yakni pasien yang dirawat di ruang CVCU dan pasien dengan post-kateterisasi jantung. Sedangkan kriteria eksklusi meliputi pasien dengan penurunan kesadaran. Analisis data menggunakan uji statistik non-parametrik Wilcoxon.Hasil: Sebelum intervensi, mayoritas responden mengalami ketergantungan sedang dan berat dengan median 9 (7-11). Setelah intervensi, mayoritas responden mengalami ketergantungan ringan dan sedang dengan median 12 (11-16). Hal ini menunjukkan adanya peningkatan kemandirian pasien dalam ADL deingan p-value = 0,000.Simpulan: Intervensi ambulasi dini yang dilakukan pasca-operasi kateterisasi jantung cukup efektif meningkatkan kemandirian pasien dalam melakukan ADL. Oleh karena itu, intervensi seperti ini dapat diberikan kepada pasien dengan kondisi serupa sehingga proses pemulihan menjadi lebih cepat.